Comparison of Two Trap Designs for Monitoring the Bark and Ambrosia Beetles (Curculionidae: Scolytinae and Platypodinae) in Mahogany Forests - Yogo Setiawan; Minhajul Qowim Yahya; Fuad Dendy; Kunihiko Hata; Jianguo Wang; Hagus Tarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Bark and ambrosia beetles are commonly found in forest ecosystems, and their fungal symbionts act as plant pathogens. Accurate information on the presence and population levels of bark and ambrosia beetles is becoming an increasingly crucial to protect the forest ecosystem. This study compared multiple-funnel and bottle traps to monitor the bark and ambrosia beetles in two types of mahogany forest. Multiple-funnel and bottle traps were made from transparent polyethylene terephthalate bottles and baited with 95% ethanol. Two different mahogany forest management (monoculture and polyculture with coffee plants) were used in this study. A total of 2,367 bark and ambrosia beetle specimens were trapped in this study. This research recorded ten genera of Scolytinae and one Platypodinae genus. Xyleborus spp., X. crassiusculus, and P. cavipennis are three predominated ambrosia beetles collected in mahogany monoculture and polyculture. Euplatypus parallelus was identified as a representative of Platypodinae. Results showed that multiple-funnel traps baited with ethanol are effective to catch individuals and several species of bark and ambrosia beetles in mahogany forests. The choice of multiple-funnel or bottle traps is an important consideration in trap-based programs for monitoring or detecting invasive species in forest ecosystems.